PHYTOCHEMICAL ANALYSES AND FREE RADICAL SCAVENGING ACTIVITY FROM TUIS (Nicolaia speciosa, HORAN) - Kojong, Novel; Monintja, John; Wehantouw, Frenly; Paendong, Edwin (Sam Ratulangi University, 2010)
Tuis (Nicolaia speciosa, Horan) is a plant which used by people to give taste and odor on food, and it also usedas herbal.The objective of this research was to determine phytochemical content and free radical scavengingactivity from Tuis. Phytochemical content in Tuis was determined by its alkaloid, steroid, flavonoid, phenolic,tannins and saponim content. Free radical scavenging activity from Tuis was determined using 1,1-difenil-2-pikrilhidrazil (DPPH) method.Tuis contain phytochemical such as alkaloids, terpenoid, saponim and tannins,although flavonoid appear only in leaves part. The highest free radical scavenging activity from Tuis was leavesextract, with IC50 1,77. Phenolic content in Tuis was believed act as antioxidant.